The Impact Of Endorphin Massage On The Efficient Production Of Postpartum Breast Milk In TPMB Sulastri, Pagelaran District, Pringsewu Regency In 2024. - Kartini; Nurhasanah, Nurhasanah; Triwahyuningsih, Ria Yulianti (Ann Publisher, 2024)
Initiating breastfeeding within the first day of delivery has been shown to decrease the likelihood of newborn mortality. It is specifically demonstrated to provide exclusive protection against diarrhea, respiratory infections, and pneumonia ASI. The project seeks to investigate endorphin massage's impact on smoothness development in postpartum women at TPMB Sulastri, S.ST., M.Kes in 2024.ASI stands for Automatic Speech Recognition. This research employs a quasi-experiment design utilizing a pretest-posttest control group strategy. The sample included of 14 participants in the intervention group and 14 participants in the control group. Purposive sampling techniques were employed. The instrument utilizes Standard Operating Procedures (SOP) and checklist sheets. A three-day Endorphin massage treatment was administered and assessed using the Mann-Whitney test. The study found that 50% of individuals had a moderate frequency of meal intake. The utilization rate of non-hormonal contraceptives was 71.4%. The weight of newborns does not exceed 100% of the BBLR. The gestational age at the time of labor is 100% accurate. The mean milk output of the intervention group was 2.6 before and 7.5 after. The mean of the control group was 2.5 before and 5.2 after. The endorphin massage significantly impacted the efficient production of breast milk in postpartum moms. This was evidenced by a p-value of 0.000 (< 0.05) and a positive Correlation Coefficient value of 0.88, indicating a highly robust association between the two variables. Ultimately, endorphin massage has a significant impact on facilitating the efficient production of breast milk in mothers throughout the postpartum period. It is desirable for lactating postpartum women to regularly engage in endorphin massage to ensure the continuous and unobstructed flow of breast milk during the entire two-year duration of breastfeeding.